KAJIAN PENERAPAN SISTEM INFORMASI DALAM AKTIFITAS PROMOSI DAN PEMESANAN PRODUK UKM STUDI KASUS CV IRWAN KONVEKSI: Small and medium enterprises, Information Systems,Promotion, and Ordering service items - Aldilla Syafri, Rista; Tri Utami, Siti (LP2M Universitas Nurdin Hamzah, 2018)
This study aims to improve the ability or understanding of CV. Irwan Konveksi in the application of the information system as a medium in the promotion and ordering of SME products of CV Irwan Konveksi. This research was conducted in a multidisciplinary manner and practitioners. The research participants were Owner and Workers at CV Irwan Konveksi. In the design of the application made there is an admin login display, order display. This view is made using programming namely PHP script language and MySQL database. The forms of software that will be implemented consist of the implementation of the website visitor access rights interface and admin access rights that aim to facilitate the business activities of CV Irwan Konveksi and assist in the promotion and ordering of products on this CV. The research was conducted in three stages, namely field research, library research and laboratory research. Obtained from the results of the study as follows: (a) UKMWho is engaged in CV services. In his business activities, Irwan Konveksi did not use technology and information systems because his business process was still applying a manual system. (b) Researchers study and design an application information system ordering and promotion. (c) Owners and Employees apply applications to facilitate work. (d) Promotion and Ordering of Cv Irwan Konveksi SME Services Products to be more effective and efficient. It can be concluded that the application of technology and information systems to the business world today plays an important role in increasing income and facilitating activities both in the production process or in the promotion process. The suggestion of this research is that Small and Medium Enterprises (UKM) are expected to apply technology and information systems in their business activities to be more efficient and effective and increase business revenues.